Interaction of amyloidogenic proteins in pancreatic β cells from subjects with synucleinopathies - Martinez-Valbuena, Ivan; Amat-Villegas, Irene; Valenti-Azcarate, Rafael; Carmona-Abellan, Maria del Mar; Marcilla, Irene; Tuñon, Maria-Teresa; Luquin, Maria-Rosario (Acta neuropathologica, 2018)
Parkinson’s disease patients experience a wide range of non-motor symptoms that may be provoked by deposits of phosphorylated α-synuclein in the peripheral nervous system. Pre-existing diabetes mellitus might be a risk factor for developing Parkinson’s disease, and indeed, nearly 60% of Parkinson’s disease patients are insulin resistant. Thus, we have investigated whether phosphorylated α-synuclein is deposited in pancreatic tissue of subjects with synucleinopathies. We studied pancreatic tissue from 39 subjects diagnosed with Parkinson’s disease, Lewy body Dementia or incidental Lewy bodies disease, as well as that from 34 subjects with diabetes mellitus and a normal neuropathological examination, and 52 subjects with a normal neuropathological examination. We examined the pancreatic accumulation of phosphorylated α-synuclein and of the islet amyloid polypeptide precursor (IAPP), an amyloidogenic protein that plays an unknown role in diabetes mellitus, but that can promote α-synuclein amyloid deposition in vitro. Moreover, we performed proximity ligation assays to assess whether these two proteins interact in the pancreas of these subjects. Cytoplasmic phosphorylated α-synuclein deposits were found in the pancreatic β cells of 14 subjects with Parkinson’s disease (93%), in 11 subjects with Lewy body Dementia (85%) and in 8 subjects with incidental Lewy body disease (73%). Furthermore, we found similar phosphorylated α-synuclein inclusions in 23 subjects with a normal neuropathological examination but with diabetes mellitus (68%) and in 9 control subjects (17%). In addition, IAPP/α-synuclein interactions appear to occur in patients with pancreatic inclusions of phosphorylated α-synuclein. The presence of phosphorylated α-synuclein inclusions in pancreatic β cells provides a new evidence of a mechanism that is potentially common to the pathogenesis of diabetes mellitus, PD and DLB. Moreover, the interaction of IAPP and α-synuclein in the pancreatic β cells of patients may represent a novel target for the development of strategies to treat these diseases.